Distinguishing Biologically Controlled Calcareous Biomineralization in Fossil Organisms Using Electron Backscatter Diffraction (EBSD) - Päßler, Jan-Filip; Jarochowska, Emilia; Bestmann, Michel; Munnecke, Axel (Frontiers in Earth Science, 2018)
Although carbonate-precipitating cyanobacteria are ubiquitous in aquatic ecosystems today, the criteria used to identify them in the geological record are subjective and rarely testable. Differences in the mode of biomineralization between cyanobacteria and eukaryotes, i.e. biologically induced calcification (BIM) vs. biologically controlled calcification (BCM), result in different crystallographic structures which might be used as a criterion to test cyanobacterial affinities. Cyanobacteria are often used as a ‘wastebasket taxon’, to which various microfossils are assigned. The lack of a testable criterion for the identification of cyanobacteria may bias their fossil record severely. We employed electron backscatter diffraction (EBSD) to investigate the structure of calcareous skeletons in two microproblematica widespread in Palaeozoic marine ecosystems: Rothpletzella, hypothesized to be a cyanobacterium, and an incertae sedis microorganism Allonema. We used a calcareous trilobite shell as a BCM reference. The mineralized structure of Allonema has a simple single-layered structure of acicular crystals perpendicular to the surface of the organism. The c-axes of these crystals are parallel to the elongation and thereby normal to the surface of the organism. EBSD pole figures and misorientation axes distribution reveal a fibre texture around the c-axis with a small degree of variation (up to 30°), indicating a highly ordered structure. A comparable pattern was found in the trilobite shell. This structure allows excluding biologically induced mineralization as the mechanism of shell formation in Allonema. In Rothpletzella, the c-axes of the microcrystalline sheath show a broader clustering compared to Allonema, but still reveal crystals tending to be perpendicular to the surface of the organism. The misorientation axes of adjacent crystals show an approximately random distribution. Rothpletzella also shares morphological similarities with extant cyanobacteria. We propose that the occurrence of a strong misorientation relationship between adjacent crystals with misorientation axes clustering around the c-axis can be used as a proxy for the degree of control exerted by an organism on its mineralized structures. Therefore, precisely constrained distributions of misorientations (misorientation angle and misorientation axis) may be used to identify BCM in otherwise problematic fossils and can be used to ground-truth the cyanobacterial affinities commonly proposed for problematic extinct organisms.